THE POWER OF WORDS: HOW LANGUAGE SHAPES OUR PERCEPTION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The purpose of this article is to find out how language affects cognitive activity and a person's perception of the world.  According to the theory of linguistic relativity, research is influenced by such processes as memory, attention and perception of time and space, structural features of language (grammar, vocabulary, and phonetics).  The paper examines empirical evidence that supports the idea that language differences influence decision-making, orientation strategy, and daily interaction with the outside world.  The results of the study show that language not only reflects, but also actively shapes cognitive experiences, which is important for creating effective teaching methods and intercultural communication.  A new perspective on the study of the influence of language on cognitive development is being opened using an integrative approach that combines practical data with theoretical models. In addition, it is the basis for further research in the field of cognitive neurolinguistics.